2021
DOI: 10.1177/08901171211048135
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exclusive Walking on Lipids and Lipoproteins in Women with Overweight and Obesity: A Systematic Review and Meta-Analysis

Abstract: Objective To evaluate the effects of walking, independent of diet and weight-loss, on lipids and lipoproteins in women with overweight and obesity. Data Source Academic Search Complete, Alternative Health Watch, Global Health, Health Source, CINAHL, MEDLINE, EMBASE, SportDiscus, and ProQuest. Study Inclusion and Exclusion Criteria (1) experiment-control design; (2) women with overweight or obesity; (3) walking as the experiment’s independent variable; (4) four or more weeks; and (5) pre- to post-assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In general, these findings are in line with those of previous studies on environmental correlates of physical activity (Cerin et al, 2017;Van Cauwenberg et al, 2018) and sedentary behaviours (Barnett et al, 2015;Cerin et al, 2020), and those on the effects of these behaviours on cardiometabolic health (Bai et al, 2022;Ballard et al, 2021;Chai et al, 2023;Wood et al, 2022).…”
Section: Neighbourhood Walkabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…In general, these findings are in line with those of previous studies on environmental correlates of physical activity (Cerin et al, 2017;Van Cauwenberg et al, 2018) and sedentary behaviours (Barnett et al, 2015;Cerin et al, 2020), and those on the effects of these behaviours on cardiometabolic health (Bai et al, 2022;Ballard et al, 2021;Chai et al, 2023;Wood et al, 2022).…”
Section: Neighbourhood Walkabilitysupporting
confidence: 91%
“…The concept of neighbourhood walkability was coined by urban planners to denote urban spaces with higher levels of density, functional mix and access networks that lend themselves to a variety of transport modes and reduce car-dependence (Frank et al, 2010). As expected, and evidenced by this study, more walkable neighbourhoods typically encourage active modes of transport (e.g., walking for transport) (Cerin et al, 2017) and engagement in leisure-time physical activity (Van Cauwenberg et al, 2018), which are beneficial to cardiometabolic health (Bai et al, 2022;Ballard et al, 2021;Lee et al, 2021). However, they are also accompanied by higher levels of air pollution (James et al, 2015) and noise (Salter et al, 2015) that can be detrimental to health (Basner et al, 2014;Gaio et al, 2019;Liu et al, 2019;Salter et al, 2015;Wang et al, 2023).…”
Section: Neighbourhood Walkabilitysupporting
confidence: 60%
“…However, the small magnitude of the changes may have little clinical impact. 1 There were no significant changes in the walking groups compared to the control groups for triglycerides (17 studies; RMD = 2.2 mg/dL; 95% CI, -8.4 to 12.8; P = .68) or high-density lipoprotein (HDL) (18 studies; RMD = 1.5 mg/dL; 95% CI, -0.4 to 3.3; P = .12). Included studies were required to be controlled but were otherwise not described.…”
Section: Exclusive Evidence Summarymentioning
confidence: 98%
“…Median TC was 206 mg/dL and median LDL was 126 mg/dL. 1 The primary outcome found that walking decreased TC and LDL levels independent of diet and weight loss. Twenty studies reported on TC and showed that walking significantly decreased TC levels compared to the control groups (raw mean difference [RMD] = 6.7 mg/dL; 95% CI, 0.4-12.9; P = .04).…”
Section: Exclusive Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation